Analisis Kestabilan Titik Setimbang Dan Kontrol Optimal Model Matematika Penyebaran Penyakit Flu Singapura Dengan Saturated Incidence Rate - Intan Permata Sari, - (2020)
Singapore flu or hand, foot and mouth disease (HFMD) is a disease with direct droplet transmission and a disease with indirect transmission, namely the use of equipment simultaneously. This disease is a contagious infectious disease caused by Coxsackievirus A type 16 (CV A16). In this thesis, an analysis of the stability of the equilibrium point of the mathematical model of the spread of the Singapore flu disease has been modified to a saturated incidence rate. Implementation of optimal control in the form of education efforts to maintain hygiene, minimize contact with infected populations and treatment. Based on the analysis of the model without control, there are two equilibrium points, namely non-endemic and endemic equilibrium points.